2019
DOI: 10.1016/j.mec.2019.e00090
|View full text |Cite
|
Sign up to set email alerts
|

Alone at last! – Heterologous expression of a single gene is sufficient for establishing the five-step Weimberg pathway in Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum can grow on d -xylose as sole carbon and energy source via the five-step Weimberg pathway when the pentacistronic xylXABCD operon from Caulobacter crescentus is heterologously expressed. More recently, it could be demonstrated that the C. glutamicum wild type accumulates the Weimberg pathway intermediate d -xylonate when cultivated in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Therefore, based on the initial rate kinetics, a model was developed for the sequential conversion of D-xylose to α-ketoglutarate and was used for experimental design (choosing appropriate enzyme concentrations), to ensure that each reaction converts 5 mM substrate completely to product in 90 min, which is suitable for NMR analysis. The NMR analysis ( 1 H-NMR and 13 C-NMR, enabled by the use of D-xylose-1-13 C) allowed for a time-resolved observation (1 data point in 1 H and 13 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. All of the enzymatically produced intermediates were in agreement with the proposed Weimberg pathway 13 .…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Therefore, based on the initial rate kinetics, a model was developed for the sequential conversion of D-xylose to α-ketoglutarate and was used for experimental design (choosing appropriate enzyme concentrations), to ensure that each reaction converts 5 mM substrate completely to product in 90 min, which is suitable for NMR analysis. The NMR analysis ( 1 H-NMR and 13 C-NMR, enabled by the use of D-xylose-1-13 C) allowed for a time-resolved observation (1 data point in 1 H and 13 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. All of the enzymatically produced intermediates were in agreement with the proposed Weimberg pathway 13 .…”
Section: Resultsmentioning
confidence: 60%
“…The second enzyme in the pathway, XLA, seems not to be essential for the pathway, as D-xylonolactone is converted to D-xylonate in a non-enzyme catalysed reaction. In engineering projects, the XLA is often omitted, as it is not essential 19 , and its omission would also prevent accumulation of D-xylonate, which was shown to be toxic in E. coli, C. glutamicum and yeast 19,[21][22][23][24][25][26] . To test whether XLA has an effect on the pathway flux, we omitted the enzyme in the reference state incubation while keeping the other four enzymes at the reference state concentrations (Supplementary Note 1).…”
Section: Model Validation In One-pot Cascade Perturbation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xylose once inside the cell gets converted to xylonolactone and then into xylonic acid on the expression of two genes namely, xylB (xylose dehydrogenase) and xylC (xylonolactonase). These two enzymes are involved in both the Weimberg and Dahms pathway where xylose is metabolized to xylonic acid (Brüsseler et al 2019). In the present study, it is observed that only the xylose dehydrogenase enzyme activity is good enough for xylonic acid production.…”
Section: Discussionmentioning
confidence: 99%